2010
DOI: 10.1007/s10457-010-9355-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of chestnut plantations for a multifunctional land use under Mediterranean conditions: effects on productivity and sustainability

Abstract: Chestnut plantations for fruit production in Northern Portugal have been subjected to intensive management system, including soil tillage, mineral fertilization and pruning. Some of these practices have no positive effect on productivity and soilplant-water relations. Other systems (e.g., no tillage with maintenance of grass cover) have been adopted, aiming a multifunctional land use, exploiting nuts, pasture and edible mushrooms. Thus, an experimental trial was installed to assess the effects of such systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Chestnut (Castanea sativa Mill.) has gained remarkable importance in recent years for fruit production in some countries of the Mediterranean basin (Martins et al 2011;Álvarez-Álvarez et al 2010). The species has several phytosanitary problems, which can severely reduce crop productivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chestnut (Castanea sativa Mill.) has gained remarkable importance in recent years for fruit production in some countries of the Mediterranean basin (Martins et al 2011;Álvarez-Álvarez et al 2010). The species has several phytosanitary problems, which can severely reduce crop productivity.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, chestnut was grown as isolated trees, small orchards, or mixed stands in agro-forestry systems, receiving reduced attention. Nowadays, chestnut trees are being planted just like other fruit tree species in true orchards and denser plantations (Martins et al 2011). The application of fertilizer is also widespread among farmers (Arrobas et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the wide range of ES supplied by these systems, they are considered as multifunctional landscape elements. Indeed, the possible role of chestnut plantations as multifunctional ecosystems has been highlighted (Martins et al, 2010). Social and demographic changes in the last century are associated with the loss of traditional cultural ecosystems (Morán-Ordóñez et al, 2011), landscapes (Martínez et al, 2010) and services (EME, 2011) in this geographical area.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of a literature review and available data, 10 potential environmental and socioeconomic factors were selected as proxy variables to run in the geographical detector. One of the most important factors affecting chestnut yield is the local geography (Martins et al, 2011). We chose elevation, slope, and aspect as proxies of the geography.…”
Section: Determinants Of Chestnut Yield and Data Collectionmentioning
confidence: 99%
“…After a literature review, we found that solar radiation was an important factor affecting chestnut yield; thus solar radiation was selected as a proxy variable for climatic conditions. The last factor we considered was the productivity condition (Martins et al, 2011), which also has a significant influence on chestnut yield. To express productivity quantitatively and spatially, the labor force and total power of agricultural machinery were selected as proxies.…”
Section: Determinants Of Chestnut Yield and Data Collectionmentioning
confidence: 99%